Odpowiedzi

2009-11-22T18:55:09+01:00
4a-2=b
3a+7b=1.5

b=4a-2
3a +7(4a-2)=1.5

b=4a-2
3a+28a-14=1.5

b=4a-2
31a-14=1.5

b=4a-2
31a=1.5+14

b=4a-2
31a=15.5|:31
a=2
b=4*2-2
b=8-2
b=6
Najlepsza Odpowiedź!
2009-11-22T18:57:12+01:00
A)
4a-2=b
3a+7b=1,5

b=4a-2
3a+7(4a-2)=1,5

b=4a-2
3a+28a-14=1,5

b=4a-2
31a=1,5+14

b=4a-2
31a=15,5

b=4a-2
a= 1/2

b=0
a= 1/2

----------------------
b)
5x=4-2y
4x+y=3

y=3-4x
5x=4-2(3-4x)

y=3-4x
5x=4-6+8x

y=3-4x
5x-8x=-2

y=3-4x
-3x=-2 /*(-1)

y=3-4x
3x=2

y=3-4x
x=2/3

y=3-4*2/3
x=2/3

y=1/3
x=2/3

----------------
c)
6x-3y=9
x+5y=-9.5

x=-9,5-5y
6(-9,5-5y)-3y=9

x=-9,5-5y
-57-30y-3y=9

x=-9,5-5y
-33y=9+57

x=-9,5-5y
-33y=66 /*(-1)

x=-9,5-5y
33y=-66

x=-9,5-5y
y=-2

x=-9,5-5(-2)
y=-2

x=1/2
y=-2
2009-11-22T19:48:53+01:00
A){4a-2=b
{3a+7b=1,5

b=-4a+2
3a+7(-4a+2)=1,5

b=-4a+2
3a-28a+14=1,5

b=-4a+2
-25a=1,5-14

b=-4a+2
25a=-12,5/"(-25)

b=-4a+2
a=0,5

b=4*0,5+2
a=0,5

b=4
a=0,5


b){5x=4-2y
{4x+y=3

5x=4-2y
y=3-4x

5x=4-2(3-4x)
y=3-4x

5x=4-6+8x
y=3-4x

-3x=-2/:(-3)
y=3-4x

x= 2/3
y=3-4x

x= 2/3
y=3-4* 2/3

x= 2/3
y=3/3 - 8/3

x= 2/3
y=-1 i 2/3


c){6x-3y=9
{x+5y=-9.5

6x-3y=9
x= -9,5-5y

6(-9,5-5y)- 3y=9
x= -9,5-5y

-57-30y-3y=9
x= -9,5-5y

-33y=66 /:(-33)
x= -9,5-5y

y=-2
x=-9,5-5 *(-2)

y=-2
x=0,5